Web-based campus election using thumb recognition / Mariam Samawi - Samawi, Mariam (2006)
For many years, paper-based ballot is used as a way to vote during campus election day. This matter put an inefficient way of voting process as students have to queue up to register their name before they can vote. Furthermore, the traditional way of voting will takes a long process and time. So, the Web-based Campus Election Using Thumb Recognition system will become the best solution for the matters, besides provide easier way of voting. Web-based Campus Election Using Thumb Recognition is a system that creates a user interface that use as a new alternative for paper-based ballot. Enhance, thumb recognition also use to provide secure environment during election process as only authorized users with thumb recognition are available to vote. So, the purpose of this project is to improve the existing campus election process. Hopefully by doing this project, the productivity and efficiency of UiTM election day will improve and become one of the most efficient election system is the world.